Perancangan Sistem Pengambilan Gambar Video Berdasarkan Pergerakan Benda Menggunakan Metode Background Subraction - Susmini I Lestariningati; Hani Irmayanti; H Hawari (Computer Engineering Departement, Universitas Komputer Indonesia, 2019)
In this journal a video capture system is designed based on the movement of objects with the background substraction method. This system is intended to provide an alternative to overcome the useless memory usage caused by CCTV cameras recording in real time even though there is no movement or event that occurs. This system uses the Raspberry Pi which is equipped with the Pi Camera, the use of this method is because this method is simple so it does not overload the Raspberry Pi. The system designed has been functionally tested according to the design, where the system has been able to record video images based on the movement of objects, and the system can be used with different light intensities, and has been able to distinguish objects based on size so the system can decide to record video.